Clinical characterisation and management outcome of obstetric patients following intensive care unit admission for COVID-19 pneumonia - Esra Aktiz Bıçak; Süleyman Cemil Oğlak (Taylor & Francis Group, 2023)
This study aims to examine the clinical characteristics and mortality-related factors of obstetric patients, who were taken to the intensive care unit due to Coronavirus Disease 2019 (COVID-19). This study included 31 patients in the peripartum period with COVID-19 pneumonia, followed up in the intensive care unit (ICU) from March 2020 to December 2020. Symptoms, laboratory values, intensive care unit duration of stay, complications, the requirement of non-invasive and invasive mechanical ventilation, and mortality were recorded. The mean age was 30.7 ± 6.2 years and the mean gestational age was 31.1 ± 6.4 weeks. Among the patients, 25.8% had a fever, 87.1% had a cough, 96.8% had dyspnoea and 77.4% had tachypnoea. Seventeen patients (54.8%) had mild, 6 (19.4%) had moderate and 8 (25.8%) had severe pulmonary involvement on computed tomography. Sixteen (51.6%) patients required high-frequency oscillatory ventilation, 6 (19.3%) patients required continuous positive airway pressure, and 5 (16.1%) patients required invasive mechanical ventilation. Sepsis complicated by septic shock and multiorgan failure occurred in 4 patients and all of them died. The ICU duration of stay was 4.9 ± 4.3 days. We have found that older maternal age, obesity, high LDH, AST, ALT, ferritin, leukocyte, CRP, and procalcitonin values, and severe lung involvement were mortality-related factors.Impact statement What is already known on this subject? Pregnant women are in the high-risk group for Covid-19 disease and its complications. Although most pregnant women are asymptomatic, severe infection-related hypoxia can cause serious foetal and maternal problems. What do the results of this study add? When we examined the literature, we found that the number of studies on pregnant women with severe Covid-19 infection was limited. For this reason, with our study results, we aim to contribute to the literature by determining the biochemical parameters and patient-related factors associated with severe infection and mortality in pregnant patients with severe Covid-19 infection. What are the implications of these findings for clinical practice and/or further research? With our study results, predisposing factors for the development of severe Covid-19 infection in the pregnant patient population and biochemical parameters that are early indicators of severe infection were determined. In this way, pregnant women in the high-risk group can be followed closely and the necessary treatments can be started quickly so disease-related complications and mortality can be reduced.